1977
DOI: 10.1002/pen.760171102
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of low density polyethylene rheological measurements, with optical and processing properties

Abstract: The processing properties of' low density polyethylene melts, such as drawdown and neck-in, and the final product properties, such as film haze and gloss, have been successfully correlated with rheological functions and the level of longchain branching. The rheological functions employed are the entrance pressure drop AP,, and the swell ratio So, determined at a specified shear stress using an orifice with a length/ diameter (LID) ratio of zero. The calculation of shear stress requires additional measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…1 and 2 is that it often serves as a good measure of the elasticity of the melt,42 and furthermore has been useful in correlating with other processing phenomena, such as die swell and melt fracture 43, 44. The choice of the low frequency at which γ ∞ was estimated rests in the fact that differences in the elastic character of various melts are magnified at low frequencies (or shear rates) because they probe the longest relaxation time behavior at these conditions 8. Furthermore, the approximation in eq.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 and 2 is that it often serves as a good measure of the elasticity of the melt,42 and furthermore has been useful in correlating with other processing phenomena, such as die swell and melt fracture 43, 44. The choice of the low frequency at which γ ∞ was estimated rests in the fact that differences in the elastic character of various melts are magnified at low frequencies (or shear rates) because they probe the longest relaxation time behavior at these conditions 8. Furthermore, the approximation in eq.…”
Section: Methodsmentioning
confidence: 99%
“…A review of some of the earlier work in this area reveals that both low and high polymer melt elasticity have been shown, either directly or as we interpret their data now, to be responsible for high haze 2, 5–8, 10, 19. For example, it has been shown that shear modification (disentanglement) of highly branched, high‐pressure (also referred to as conventional), low‐density PE (HP‐LDPE) resins resulted in an improvement (decrease) in blown film haze due to a decrease in the melt elasticity 5, 19.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Since the values of temperature and shear rate employed in an MFI test differ substantially from those encountered in actual large scale processes, MFI does not correlate directly with processing behavior, as has been shown by Smith3' as well as Shida et al 38 As far as processing is concerned, both high and low shear viscosities of the material are critical. Low shear properties are important in applications where melt strength, sagging are critical such as in blow molding and coating.…”
Section: Rheological Considerationsmentioning
confidence: 97%
“…Therefore, converters have to employ an appropriate grade that have a good balance between the maximum drawdown speed and the neck-in level. For the purpose, extensive efforts have been carried out to correlate the processability with the polymer structure [2][3][4][5] or the rheological properties [5][6][7][8][9][10][11], which can be evaluated in a laboratory scale, in order to avoid the processing trial by a manufacturing machine.…”
Section: Introductionmentioning
confidence: 99%